2012
DOI: 10.1161/strokeaha.111.621029
|View full text |Cite
|
Sign up to set email alerts
|

Child-Mediated Stroke Communication

Abstract: Background and Purpose Low thrombolysis rates for acute ischemic stroke is linked to delays in seeking immediate treatment due to low public stroke awareness. We aimed to assess whether “Child-Mediated Stroke Communication” (CMSC) could improve stroke literacy parents of children enrolled in a school-based stroke literacy program called Hip Hop Stroke (HHS). Methods Parents of children aged 9 to 12 years from two public schools in Harlem, NYC, were recruited to participate in stroke literacy questionnaires b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
73
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 23 publications
(28 reference statements)
1
73
0
3
Order By: Relevance
“…We and others recently reported the results of studies of stroke educational campaigns for teenagers. [1][2][3][4][5] These results suggest that educating the youth on stroke is effective in spreading stroke knowledge to their families indirectly by communication among their family members.…”
mentioning
confidence: 82%
“…We and others recently reported the results of studies of stroke educational campaigns for teenagers. [1][2][3][4][5] These results suggest that educating the youth on stroke is effective in spreading stroke knowledge to their families indirectly by communication among their family members.…”
mentioning
confidence: 82%
“…1 Programs targeting children may equip them with the ability to recognize stroke symptoms and call 911, [1][2][3] but long-term follow-up data are scarce. Interventions have engaged elementary and middle school children, with program follow-up duration ranging from 10 days 4 to 2 months.…”
mentioning
confidence: 99%
“…In prior studies, we demonstrated the efficacy of HHS to improve knowledge of the children at 3 months 2 and of their parents 1 week after the intervention period. 3 In this study, we hypothesized that stroke knowledge among children will be retained 15 months after the completion of the curriculum.…”
mentioning
confidence: 99%
“…9 A larger randomized trial of Hip Hop is ongoing in New York City. 10,11 The community placed health-literate beauty shop intervention in African American women improved knowledge of stroke warning signs and calling 911, and this knowledge was sustained for ≥5 months. 12 Although these studies have focused on increased knowledge and behavioral intent (ie, will call 911), data from the Stroke Warning and Information and Faster Treatment Study (SWIFT) specifically measured preparedness outcomes in a randomized group of 1200 stroke and transient ischemic attack (TIA) patients.…”
Section: June 2013mentioning
confidence: 99%